Testando as previsões de trade-off e pecking order sobre dividendos e dívida no Brasil - Silva, Júlio Cesar G. da; Brito, Ricardo D. (Estudos Econômicos (São Paulo), 2005)
This article shows that the Brazilian companies have a low target payout ratio, although the local tax code favors dividends' distributions. The dividends paid present fast adjustment to current earnings, but part of the short-term variation in earnings is still absorbed by debt. Confirming predictions shared by the trade-off and pecking order models, more profitable firms and less levered firms have higher dividend payouts. Consistent with the pecking order model, dividends do not vary in the short-term to accommodate investments. Finally, more profitable firms and firms with fewer investments are less levered, accepting the pecking order hypothesis against the trade-off one.